May 1998 Mass Riots in Jakarta: A Holistic and Contextual Analysis of Critical Political Communication - Wahyu Iryana; Muhamad Bisri Mustofa (History Department, Semarang State University and Historian Society of Indonesia, 2023)
The discussion of the May 1998 mass riots in Jakarta did not only focus on demonstrations carried out by thousands of people. The existence of related events around Jakarta's capital city caused mass panic due to political problems in the bureaucracy, public anxiety about security in the capital city of Jakarta, and the emergence of public panic due to the economic crisis and anti-Chinese issues. Using a critical political communication approach that takes into account the holistic and contextual factors surrounding the event. By analyzing the political communication processes that took place during the event, this paper identifies the factors that contributed to the riot and explores how a critical political communication approach can be used to prevent similar incidents in the future. This approach focuses on increasing public participation in the political process and promoting accountability among political leaders, which can reduce political tension and the likelihood of riots. The results of the research can be concluded that the process of the May 1998 mass rioting in Jakarta was an act of protest against the government, which was found to be an injustice to society. It started from the economic crisis that caused price increases and the weakening of the Rupiah value, which resulted in soaring Indonesia's debt to foreign countries, the corruption cases carried out by President Soeharto and his cronies. The occurrence of Nepotism made ministers part of President Soeharto's family, and the demonstrations also demanded the downfall of the New Order regime. Pembahasan kerusuhan massal Mei 1998 di Jakarta tidak hanya fokus pada demonstrasi yang dilakukan ribuan orang. Adanya kejadian terkait di sekitar ibu kota Jakarta menimbulkan kepanikan massal akibat permasalahan politik di birokrasi, kegelisahan masyarakat terhadap keamanan di ibu kota Jakarta, serta munculnya kepanikan masyarakat akibat krisis ekonomi dan isu anti Tionghoa. Menggunakan pendekatan komunikasi politik kritis yang mempertimbangkan faktor holistik dan kontekstual seputar peristiwa tersebut. Dengan menganalisis proses komunikasi politik yang terjadi pada peristiwa tersebut, tulisan ini mengidentifikasi faktor-faktor yang berkontribusi terhadap kerusuhan dan mengeksplorasi bagaimana pendekatan komunikasi politik kritis dapat digunakan untuk mencegah kejadian serupa di masa depan. Pendekatan ini berfokus pada peningkatan partisipasi masyarakat dalam proses politik dan mendorong akuntabilitas di antara para pemimpin politik, sehingga dapat mengurangi ketegangan politik dan kemungkinan terjadinya kerusuhan. Hasil penelitian dapat disimpulkan bahwa proses terjadinya kerusuhan massal Mei 1998 di Jakarta merupakan sebuah aksi protes terhadap pemerintah yang dinilai memberikan ketidakadilan terhadap masyarakat. Bermula dari krisis ekonomi yang menyebabkan kenaikan harga dan melemahnya nilai Rupiah yang mengakibatkan melonjaknya hutang Indonesia ke luar negeri, kasus korupsi yang dilakukan oleh Presiden Soeharto dan kroni-kroninya. Terjadinya Nepotisme menjadikan menteri sebagai bagian dari keluarga Presiden Soeharto, dan demonstrasi juga menuntut jatuhnya rezim Orde Baru.